Cash Mobilization in Ghana: An Empirical Evaluation of The Effectiveness of E-Zwich Smart Card - Poku, Kwasi; Adu, John Kwame; Osei-Asibe, Boakye (Advances in Social Sciences Research Journal, 2014)
Over the years there has been a progression of value transfer systems starting from barter, through bank notes, payment orders, cheques and later Credit Cards (Asokan et al., 2000). This has finally evolved into electronic payment on the Internet. This research therefore assesses the adoption of cash mobilization system using e-zwich payment system in Ghana. The population for the research was clients and merchants of E-zwich in the Kumasi Metropolis. The population included staffs of the various banks in the Metropolis that have E-zwich services. A sample size of sixty (60) clients and five (5) staff each from five (5) Banks and twenty (20) merchants were selected. It was found among others that, merchants are raising concerns with buying and loading of credit units unto the POS device, unavailability of thermal roll on the market and network connectivity issues while performing “profile download” – a very important activity before transactions can occur on the POS device. Compounding to the issues, clients are also facing the unavailability of enough merchants in the Metropolis while most of the small available merchants they visit do not have their POS systems working effectively. However, it is recommended among others that, the revolution of the e-zwich system should be targeting teenagers and young adults who receive transfers from their parents or guardians and possess a sizeable amount of money but are often ineligible to open a bank account which will allow a greater proportion of funds to remain within the banking system until they are spent.